Caracterização do mecanismo de ação antineoplásica do complexo à base de cobre DRI12 (cobre II e ácido 4 fluorofenoacético hidrazida e 1,10 fenantrolina) e desenvolvimento de carreadores lipídicos nanoestruturados NLC/DRI12 para o tratamento tumoral - Machado, Pedro Henrique Alves (2024)
Cancer is recognized as a major public health problem, leading to the death of thousands of people every year, which has led to the need to develop more effective therapeutic techniques. Chemotherapy is a widely applied therapeutic approach, and at this point, metal-based chemotherapies gained prominence with the emergence and use of cisplatin, leading to the search for new metallocomplexes with better antineoplastic activity and milder side effects. Copper is an endogenous micronutrient and is essential for the functioning of the human body. It is known that tumor tissues have a higher concentration of copper, making the metal interesting for the development of chemotherapy drugs. Copper is a redox-active metal, which gives it the ability to induce ROS (reactive oxygen species), and when coordinated with other ligands its ability to interact with the DNA of tumor cells is increased thanks to the synergy of the constituents of the coordination metal complex. In this sense, the present work presents the in vitro and in vivo antitumor action of the copper (II) complex associated with 4-fluorophenoxyacetic acid (hydrazide and 1,10-phenanthroline) DRI12 and its formulation in nanostructured lipid carriers NLC/DRI12. The use of drug delivery systems is gaining prominence because they can solve problems related to the permanence, delivery and reduction of side effects of pharmacological actives. The DRI12 complex and the NLC/DRI12 nanoformulation demonstrate antitumor potential with superior results (IC50 and IS) compared to cisplatin and other copper-based complexes in the tumors used in this work (B16F10 and TG180). The results obtained make the copper metallocomplex DRI12 and its nanoformulation NLC/DRI12 a promising candidate for chemotherapy.